Protection of Micro, Small, Medium Enterprises (MSMEs) Related to the Prohibition of Importing Used Clothing Perspective of Maslahah Mursalah Theory - Marpaung, Fachrunnisa Windi; Harahap, Mhd Yadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Trade Regulation Number 40 of 2022 issues a policy prohibiting the import of used clothing in Indonesia. This policy has a detrimental impact on imported used clothing traders, especially those in Kisaran City. For this reason, the protection of micro, small, and medium enterprises (MSMEs) in the local clothing sector must receive attention. From the perspective of maslahah mursalah, it takes into account the public benefit and the interests of society at large, including in issuing laws, including Minister of Trade Regulation Number 40 of 2022, which was issued to improve market prices due to the large number of buyers of used clothes. However, on the other hand, it needs to be understood that the government must also pay attention to the welfare of second-hand clothing sellers who will of course lose their jobs because of the policies made. This research concludes that the government can take several actions, such as providing training or outreach related to the development of MSMEs so that people can upgrade their skills and can make products that are equivalent to foreign goods so that in the future there is no need to import used goods from abroad. This research uses empirical legal research methods, by collecting data on the direct effects experienced by MSMEs, especially sellers of imported second-hand goods, as well as the protection provided by the government to them according to Maslahah Mursalah.